Web 2 vs. Web 3 Paths to the Metaverse: Who Is Leading? Who Should Lead? - Le Kuai; Mary Lacity; Jeffrey K. Mullins (The Journal of The British Blockchain Association, 2023)
Our research investigates two questions: Who is leading the metaverse? Who should lead? The questions are important because metaverse will have significant consequences for individuals, businesses, and society. We examined the current leaders of metaverse on two evolutionary paths, namely Web 2 and Web 3. Based on regulatory reports, corporate press releases, and patents, we found that only a handful of Web 2 companies are “all-in” on metaverse, and at least one of these enterprises, Meta, is on track to end up as a dominant platform provider. Based on market capitalization, user activity, and patents, only a handful of Web 3 communities are emerging. Despite the hype, we are still in the early days for metaverse on both evolutionary paths. As far as who should lead, we advocate for Web 3 because it benefits more users, content creators, and businesses. However, the future of metaverse is not deterministic and it will emerge from the choices we make today. We offer recommendations on how scholars and companies can support the Web 3 path to the metaverse.